A Simple and Convenient Synthesis of (1, 4)-Benzoxazino-(2, 3 b)-Phenoxazines - Ojha, K.G.; Adwani, P.; Kawadiya, Mahaveer; Tanwar, Mukesh (Asian Journal of Chemistry, 2010)
Substituted 6, 13-dihalo-(1, 4-)-benzoxaion-(2, 3b)-phenoxazines(IV) have been synthesised by condensing arylamines with halogeno-p-benzoquinones followed by cyclisation of the resulting diarylamino quinone (III) with benzolyl chloride in nitro benzene.